Determination of In Vitro Antimicrobial Activity of Five Sri Lankan Medicinal Plants against Selected Human Pathogenic Bacteria - Manikkuwadura Hasara Nethmini De Zoysa; Hasanga Rathnayake; Ruwani Punyakanthi Hewawasam; Weerasinghe Mudiyanselage Dilip Gaya Bandara Wijayaratne (International Journal of Microbiology)
Introduction. Antibiotic resistance is one of the greatest threats of the 21st century. Scientists search for potential antimicrobial sources that can cope with antibiotic resistance. Plants used in traditional medicine can be identified as potential candidates for the synthesis of novel drug compounds to act against antibiotic-resistant bacteria. Objective. To determine the potential antimicrobial effects of ethanol, aqueous, and hexane extracts of five Sri Lankan medicinal plants against four human pathogens. Methods. Asparagus falcatus (tubers), Asteracantha longifolia (whole plant), Vetiveria zizanioides (roots), Epaltes divaricata (whole plant), and Coriandrum sativum (seeds) were used in the study. Plant extracts were screened against four clinically important Gram-positive and Gram-negative bacterial strains, Staphylococcus aureus (ATCC 25923), Escherichia coli (ATCC 25922), Pseudomonas aeruginosa (ATCC 27853), and Klebsiella pneumoniae (ATCC 700603). Antibacterial activity of plant extracts were monitored using the agar disc diffusion method. Eight concentrations of each positive plant extract were used to determine the minimum inhibitory concentration (MIC) by 5-fold dilution of plant extracts yielding a serial dilution of the original extract. Results. Ethanol, aqueous, and hexane extracts of E. divaricata gave the maximum zones of inhibition of 16.3 mm, 7.4 mm, and 13.7 mm and MIC values of 0.48 mg/ml, 1.2 mg/ml, and 1.6 mg/ml, respectively, against S. aureus. Ethanol and hexane extracts of V. zizanioides gave the maximum zones of inhibition of 12.1 mm and 11.4 mm and MIC values 2.4 mg/ml and 0.003 mg/ml, respectively, against S. aureus. None of the other plants were effective against any microorganism used for the study. Conclusions. It can be concluded that E. divaricata and V. zizanioides crude ethanol, aqueous, and hexane extracts exhibited significant in vitro antibacterial activity against S. aureus, and the active compounds isolated from them can be potential sources for the synthesis of antibacterial drugs.